ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI KECEMASAN MATEMATIKA SISWA - Genit Anggarawati; Dina Prasetyowati; Muhammad Saifuddin Zuhri (STKIP Subang, 2023)
Students' mathematical problem solving abilities can be influenced by students' mathematical anxiety. This research aims to 1) determine the mathematics problem solving abilities of students with high mathematics anxiety, 2) to determine the mathematics problem solving abilities of students with moderate mathematics anxiety, 3) to determine the mathematics problem solving abilities of students with low mathematics anxiety. This type of research is qualitative descriptive research. This research was carried out at SMP Negeri 1 Talun, Pekalongan Regency in 2023/2024. The subjects of this research were 6 students in class VIII-A consisting of 2 students with high math anxiety, 2 students with moderate math anxiety, and 2 students with low math anxiety. The data collection methods used were mathematics anxiety questionnaires, problem solving ability tests, and interviews. Meanwhile, the triangulation used in this research is method triangulation and source triangulation. The results of this research show that 1) students with high mathematics anxiety have not been able to fulfill the problem solving indicators according to Polya, 2) students with moderate mathematics anxiety have only been able to fulfill 1 problem solving indicator according to Polya, and 3) students with low mathematics anxiety have been able to fulfill the solving indicators problem according to Polya.